The Role of Mitophagy in Skeletal Muscle Damage and Regeneration. - Chatzinikita, Eirini; Maridaki, Maria; Palikaras, Konstantinos; Koutsilieris, Michael; Philippou, Anastassios (Cells, 2023)
Mitochondria are cellular organelles that play an essential role in generating the chemical energy needed for the biochemical reactions in cells. Mitochondrial biogenesis, i.e., de novo mitochondria formation, results in enhanced cellular respiration, metabolic processes, and ATP generation, while autophagic clearance of mitochondria (mitophagy) is required to remove damaged or useless mitochondria. The balance between the opposing processes of mitochondrial biogenesis and mitophagy is highly regulated and crucial for the maintenance of the number and function of mitochondria as well as for the cellular homeostasis and adaptations to metabolic demands and extracellular stimuli. In skeletal muscle, mitochondria are essential for maintaining energy homeostasis, and the mitochondrial network exhibits complex behaviors and undergoes dynamic remodeling in response to various conditions and pathologies characterized by changes in muscle cell structure and metabolism, such as exercise, muscle damage, and myopathies. In particular, the involvement of mitochondrial remodeling in mediating skeletal muscle regeneration following damage has received increased attention, as modifications in mitophagy-related signals arise from exercise, while variations in mitochondrial restructuring pathways can lead to partial regeneration and impaired muscle function. Muscle regeneration (through myogenesis) following exercise-induced damage is characterized by a highly regulated, rapid turnover of poor-functioning mitochondria, permitting the synthesis of better-functioning mitochondria to occur. Nevertheless, essential aspects of mitochondrial remodeling during muscle regeneration remain poorly understood and warrant further characterization. In this review, we focus on the critical role of mitophagy for proper muscle cell regeneration following damage, highlighting the molecular mechanisms of the mitophagy-associated mitochondrial dynamics and network reformation.
Keywords: Autophagy; Mitochondria; Mitochondrial Dynamics; mitophagy; Muscle, Skeletal